2021
DOI: 10.2147/ijgm.s300775
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Exome Sequencing for Identifying Genetic Causes of Intellectual Developmental Disorders

Abstract: Background Intellectual developmental disorders (IDD) generally refers to the persistent impairment of cognitive activities and mental retardation caused by physical damage to the brain or incomplete brain development. We aimed to explore its genetic causes. Methods In this study, 21 IDD patients were recruited. The Gesell developmental scales (GDS) and Wechsler intelligence scale for children (WISC) were used to assess the impaired level of intellectual development for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In Table 1 , Group A also includes seven families that we previously reported on with loss or reduced function [ 5 ]. It also includes data from 23 families whose variant was recurrent with one in our cohort, for whom only limited data was available in public databases (ClinVar, DECIPHER, LOVD) as of the 25th May 2022, or from publications from other groups [ 7 , 8 , 11 , 31 ]. We included these families as further evidence of the pathogenicity of these recurrent variants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Table 1 , Group A also includes seven families that we previously reported on with loss or reduced function [ 5 ]. It also includes data from 23 families whose variant was recurrent with one in our cohort, for whom only limited data was available in public databases (ClinVar, DECIPHER, LOVD) as of the 25th May 2022, or from publications from other groups [ 7 , 8 , 11 , 31 ]. We included these families as further evidence of the pathogenicity of these recurrent variants.…”
Section: Resultsmentioning
confidence: 99%
“…This study thus brings the total number of individuals with (likely) pathogenic variants in CLCN4 to a total of 122: 58 males and 64 females. For 20 of the females, parental studies demonstrated the variant to be de novo , while the other 44 females were identified as being heterozygous for a CLCN4 variant only after a relative (usually a son, but on two occasions a daughter) was identified in their family to have CLCN4 -related condition [ 1 , 2 , 5 , 7 , 11 , 31 ]. The clinical features of this expanded cohort are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole Exome Sequencing emerged as a pivotal tool in diagnosing rare genetic disorders, including DYRK1A mutations. This technique offers a comprehensive view of genetic variants, aiding clinicians in unraveling complex cases [ 7 ]. Hence, the patient presented in this case was diagnosed based on Whole Exome Sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Limited by regional economy, health and culture, and other factors, minority areas have always lagged behind other areas. It is difficult for them to effectively utilize existing child health resources, especially ethnic minorities in remote border areas, so health level of children is far below the national average [ 1 ].…”
Section: Introductionmentioning
confidence: 99%